PENGARUH PEMANFAATAN MEDIA SOSIAL INSTAGRAM TERHADAP KREATIVITAS BELAJAR PADA REMAJA KELAS VII - Rubiyati Rubiyati; Muhamad Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2018)
AbstractInstagram is a photo sharing service app that allows users to goto, filtering and disseminating social networks, including instagram property own. The influence of social media instagram on creativity of adolescent learning creativity is the thing which is important, because it is important for teenagers to determine the effect of the use of instagram on the creativity of learning for adolescents can use instagram wisely so as to give a positive effect to stimulate his learning creativity. The formulation of the problem in this study is how is the influence of the use of social media instagram on the creativity of learning in adolescents class VII SMP Negeri 23 Pontianak?. The method used is descriptive method and the form of research is the form of study relationship studies. Population in this study as much as 236 and samples 64 students SMP Negeri 23 Pontianak. Data collection tecniques used are indirect communication techniques and data collection tools by questionnaire. While the technique of data analysis using the formula percentage. Based on the results of data analysis, the influence of social media utilization instagram on creativity of learning in adolescent class VII SMP Negeri 23 Pontianak good influence on learning creativity.Keywords : Utagraph utilization, Learning creativity